2019
DOI: 10.13005/bpj/1656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relaxation Therapy and Vitamin C Supplementation on Stress and CD4 Levels of Mentall Illness Patients

Abstract: A significant increase in the number of mental disorders has been a phenomenon in the world, including Indonesia. It may indicate by the increasing number of the inpatients of mental hospitals. The study aims to determine the effect of the combination of psychosocial therapy and vitamin C on the stress and immunity level of patients with mental disorders. This study applied pre-experimental design on three groups in which each group consists of seven respondents with an assumption that 20% will be lost of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…At the functional level, a unique microbial metabolic pathway profile was present in TLEA's gut, such as ascorbic acid synthesis. Vitamin C(ascorbic acid) is a well-known antioxidant that is said to be involved in treating anxiety in humans (Oliveira et al, 2015 ; Pratiwi et al, 2019 ). Vitamin C supplementation at 3,000 mg daily lowered subjective stress against acute psychological stressors (Brody et al, 2002 ), and a relief effect on anxious mood was observed after vitamin C administration in healthy individuals (Oliveira et al, 2015 ; Moritz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the functional level, a unique microbial metabolic pathway profile was present in TLEA's gut, such as ascorbic acid synthesis. Vitamin C(ascorbic acid) is a well-known antioxidant that is said to be involved in treating anxiety in humans (Oliveira et al, 2015 ; Pratiwi et al, 2019 ). Vitamin C supplementation at 3,000 mg daily lowered subjective stress against acute psychological stressors (Brody et al, 2002 ), and a relief effect on anxious mood was observed after vitamin C administration in healthy individuals (Oliveira et al, 2015 ; Moritz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%